Sexual orientation in school context: official speech versus pedagogic quotidian - Almeida, Sandra Aparecida de; Nogueira, Jordana de Almeida; Lacerda, Sheylla Nadjane Batista; Torres, Gilson Vasconcelos (Revista de Enfermagem UFPE on line, 2010)
ABSTRACT Objective: to analyze under the view of managers of primary school of the city of Cajazeiras/PB, how the theme “sexual orientation” has been incorporated in the pedagogic practices. Methodology: this is about a qualitative research performed in 2008, with eight managers of public schools, after has been approved by the Ethics Committee of the Federal University of Paraiba/UFPB through protocol number 1075. The semi-structured interview was elected as technique of investigation, and the empiric material obtained was submitted to the Technique of Analysis of Content, thematic modality. Results: it was highlighted that there is a commitment of the managers towards the insertion of the sexual orientation in the school context and that investments in the continued formation of educators have been done. However they recognize that the lacks of technical/ emotional preparation of the educators interfere in the effective deepening of this content. Attention is given to natural sciences and prevention education actions. Conclusion: intervention programs that reflect an orientation and/or political decision in the practice previously taken, could not guarantee their execution and/or deployment, as they require the understanding of the context that shapes and determines the representation of the actors. Descriptors: sexuality; sexual orientation; sexual behavior RESUMO Objetivo: analisar sob a ótica dos gestores do ensino fundamental da cidade de Cajazeiras/PB como o tema “orientação sexual” vem sendo incorporado nas práticas pedagógicas. Metodologia: pesquisa qualitativa, realizada em 2008, envolvendo oito gestores das escolas públicas, após aprovação do Comitê de Ética em Pesquisa da Universidade Federal da Paraíba, sob o protocolo 1075. Elegeu-se a entrevista semi-estruturada com técnica de investigação e o material empírico obtido foi submetido à Técnica de Análise de Conteúdo, modalidade temática. Resultado: evidenciou-se que há comprometimento por parte dos gestores no que tange a inserção da orientação sexual no contexto escolar e que vem sendo feito investimentos na formação continuada dos educadores. Entretanto, reconhecem que a falta de preparo técnico/emocional dos educadores interfere na efetivação e aprofundamento desse conteúdo. Privilegia-se a área de ciências naturais e enfoque preventivista das ações educativas. Conclusão: programas de intervenção que na prática traduzem uma orientação e/ou decisão política previamente tomada, não garantem sua execução e/ou implantação, pois exigem a compreensão do contexto que molda e condiciona as representações dos atores. Descritores: sexualidade; orientação sexual; comportamento sexual RESUMEN Objetivo: analizar desde la perspectiva de los gestores de la enseñanza básica de la ciudad de Cajazeiras/PB, de qué forma el tema “orientación sexual” viene siendo incorporado a las prácticas pedagógicas. Metodología: investigación cualitativa, llevada a cabo en 2008 participaron ocho directores de las escuelas públicas, aprobado por el Comité de Ética de la Universidad Federal de Paraíba, protocolo 1075. Elegido para ser las entrevistas semi-estructuradas con la investigación técnica y empírica material obtenido fue sometido a la técnica de análisis de contenido, modalidad temática. Resultados: se evidencia que hay un compromiso por parte de los gestores en cuanto a la inserción de la orientación sexual en el contexto escolar, y que se viene invirtiendo en la formación permanente de los educadores. Sin embargo, se reconoce que la falta de preparación técnico/emocional de los educadores interfiere en la efectividad y profundización de ese contenido. Se presta atención a las ciencias naturales y las acciones de prevención de la educación. Conclusión: se considera que programas de intervención que, en la práctica, tienen una orientación y/o decisión política previa, no garantizan su ejecución y/o implantación, ya que exigen la comprensión del contexto que modela y condiciona las representaciones de los actores. Descriptores: sexualidad; orientación sexual; comportamiento sexual.